The Gaia-ESO survey: detailed abundances in the metal-poor globular cluster NGC 4372 - San Roman, Izaskun; Muñoz, C.; Geisler, D.; Villanova, S.; Kacharov, Nikolay; Koch-Hansen, Andreas; Carraro, G.; Tautvaišiene, G.; Vallenari, A.; Alfaro, E. J.; Bensby, T.; Flaccomio, E.; et al. (Astronomy and astrophysics, 2015)
We present the abundance analysis for a sample of 7 red giant branch stars in the metal-poor globular cluster NGC 4372 based on UVES spectra acquired as part of the Gaia-ESO Survey. This is the first extensive study of this cluster from high-resolution spectroscopy. We derive abundances of O, Na, Mg, Al, Si, Ca, Sc, Ti, Fe, Cr, Ni, Y, Ba, and La. We find a metallicity of [Fe/H] = −2.19 ± 0.03 and find no evidence of any metallicity spread. This metallicity makes NGC 4372 one of the most metal-poor Galactic globular clusters. We also find an α-enhancement typical of halo globular clusters at this metallicity. Significant spreads are observed in the abundances of light elements. In particular, we find a Na-O anticorrelation. Abundances of O are relatively high compared with other globular clusters. This could indicate that NGC 4372 was formed in an environment with high O for its metallicity. A Mg-Al spread is also present that spans a range of more than 0.5 dex in Al abundances. Na is correlated with Al and Mgabundances at a lower significance level. This pattern suggests that the Mg-Al burning cycle is active. This behavior can also be seen in giant stars of other massive, metal-poor clusters. A relation between light and heavy s-process elements has been identified.
Gesehen am 10.06.2020